Two new species of the Solanum asterophorum species group (Solanum subg. Leptostemonum, Solanaceae) from the Brazilian Atlantic Forest - Gouvêa, Yuri Fernandes; Stehmann, João Renato (Phytotaxa, 2016)
Two new species of “spiny” Solanum (subgenus Leptostemonum), endemic to the Atlantic Forest of the southeastern region of Brazil, are described. Solanum igniferum and Solanum sessilantherum are morphologically related to Solanum asterophorum. Solanum igniferum inhabits the southern region of Espírito Santo State, and can be primarily distinguished from S. asterophorum by its orange-colored to ferruginous vestiture and the pedicels that are straight, or nearly so, keeping the flower buds erect to patent. Solanum sessilantherum differs chiefly from S. asterophorum also by pedicels that are straight, or nearly so, keeping the floral buds erect to patent, loosely arranged inflorescences, with armed axis, usually with unpaired pedicel insertion points when fully developed, and inconspicuous filaments giving the anthers a sessile appearance. Full descriptions, illustrations, distribution map and conservation status are provided, as well as comparative notes on the morphology, geography and some ecological aspects.